Non-cooperative and cooperative policy reforms under uncertainty and spillovers - Carsten Hefeker; Michael Neugart (Philipps-University Marburg, School of Business and Economics, 2017)
When countries need to implement costly economic policy reforms, these often imply uncertainties about their effectiveness for the home country and their spillovers to other countries. We develop a model to show that under these circumstances countries implement too few or too many policy reforms. From a social perspective, too many reforms follow if the spillover effects of reforms become sufficiently uncertain. Since centralization of policies to correct inefficient policies is often not possible, we look for alternative instruments that can restore the efficient level of reforms. We compare subsidizing reform e orts with insuring against bad outcomes, and argue that subsidies are advantageous in terms of requiring less information for implementation.
Keywords: F55; H70; O30; 330; policy reforms; spillovers; policy uncertainty; free-riding; subsidy; insurance